Bioactive dammarane triterpenoid saponins from the leaves of Cyclocarya paliurus. (March 2021) - Zhou, Xian-Li; Li, Shan-Bin; Yan, Meng-Qi; Luo, Qin; Wang, Li-Sheng; Shen, Ling-Li; Liao, Mei-Lian; Lu, Cai-Hua; Liu, Xia-Yan; Liang, Cheng-Qin
Abstract: Thirteen undescribed dammarane triterpenoid saponins (cypaliurusides A–M), including eleven seco-dammarane type triterpenoids, were isolated from Cyclocarya paliurus . Each of these compounds has the unique feature of having a monosaccharide attached to C-11, rather than C-12, compared to the same type of saponins found in this plant. The structures of them were determined by comprehensive analysis of 1D, 2D NMR and HRESIMS data. Cypaliuruside J showed significant α -glucosidase inhibitory effect with IC50 value of 2.22 ± 0.13 μM. In addition, Cypaliurusides F and K exhibited modest cytotoxic activities against selected human cancer cell lines in vitro, with IC50 values ranging from 4.61 ± 0.13 to 15.23 ± 3.88 μM. Graphical abstract: Image 1 Highlights: Thirteen undescribed dammarane triterpenoid saponins were found . Each of the saponins has a monosaccharide attached to C-11, rather than C-12. Cypaliuruside J exhibited significant inhibitory effect on α -glucosidase. Cypaliurusides F and K showed modest cytotoxic activities .